Human-wildlife coexistence through the lens of fishermen’s knowledge and lived experience - Molly Glickman; Michelle María Early Capistrán; Dick Ogg; Larry B. Crowder (npj Ocean Sustainability)
Abstract Climate change-related shifts in marine resource availability and species behavior are increasing rates of human-wildlife conflict (HWC). Although this trend poses significant risks to both human livelihoods and conservation efforts, strategies to resolve HWC focus largely on ecological outcomes, overlooking key impacts and contributions of human resource users. Here, we draw on the case study of whale entanglement in the Dungeness crab (Metacarcinus magister) fishery in California, U.S.A. to demonstrate the promise of integrating – and the consequences of neglecting – the voice and expertise of fishing communities. Semi-structured interviews with 27 commercial fishermen across nine towns in California revealed the diverse sociocultural impacts of HWC – often converging on livelihood and identity losses – as well as fishermen’s potential role in addressing HWC as long-time experts in the marine ecosystem. Our findings highlight pathways for achieving human-wildlife coexistence, underscoring the need to engage the knowledge and lived experience of local communities affected by HWC.